The Analysis of Gender in Metaphors: Pramoedya Ananta Toer’s Novel - Ayu Bandu Retnomurti; Nurmala Hendrawaty (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Metaphor as one of the figurative languages supposition that the more frequently used, both as a sweetener and to get people interested in reading. Not easy to determine the exact word or phrase to be compared as if the word or phrase does not fit will obscure even be able to eliminate its meaning. The purpose of this research is to explain the specificity in the use of metaphor, especially concerning the types of gender. This research uses the qualitative method to analyze the data based on the context of meaning that enveloped it. In this research, it was found metaphors that have a particular use, especially concerning gender such as You, The Girl from the Coast, The Girl, The Flower of the Town, Village Kembang, Night Butterfly, the moon, Spanish Guitar, which are the images that have the specific use to describe the topic of women. While, Governor, Daendels, The Village Chief, An Owl, The Servant, Sea Lizards, Blackguard, the Old Man, Garong Cat are the uses of imaging have the specific in describing the topic of men. The implication of this research can be expanded by comparing the metaphors that have imaging sexed women in English would be translated using the metaphor sexed women also in Indonesian, and how metaphors that have imaging sexed man would translate metaphors imagery sexed man also has answered through this research. The recommendation of the researchers suggests for the next researcher to discuss the other figurative languages such as simile, hyperbole, paradox by using its markers.